Exploring the Impact of Olive-Derived Bioactive Components on Gut Microbiota: Implications for Digestive Health - Manuel Garrido-Romero; Marina Díez-Municio; Francisco Javier Moreno (Foods, 2025)
Recent advances highlight the crucial role of the gut microbiota in human health and disease, with dietary components emerging as powerful modulators of microbial communities. This review synthesizes current evidence on the effects of olive-derived bioactive compounds, including polyphenols (e.g., hydroxytyrosol, oleuropein or tyrosol), triterpenes and other phytochemicals on gut microbiota composition and function. These compounds have been shown to enhance beneficial bacterial populations such as Lactobacillus and Bifidobacterium, reduce potentially pathogenic taxa, and promote the production of short-chain fatty acids and other health microbial metabolites, reinforcing intestinal barrier integrity. In vitro, in vivo, and clinical studies also reveal the potential of olive bioactives to ameliorate metabolic, inflammatory, and neurocognitive disorders through gut-microbiota-brain axis modulation. Despite promising results, key challenges remain, including interindividual microbiota variability, lack of standardized intervention protocols, and limited human clinical trials. Addressing these gaps through robust translational research could pave the way for microbiota-targeted, personalized nutritional strategies based on olive-derived compounds.